Efektivitas Penerapan Teknik Bermain Peran (Role Playing) Melalui Bimbingan Kelompok Untuk Peningkatan Self Esteem Siswa - Selviana Defonora Nagul; Rosa Mustika Bulor; Dhiu Margaretha (Morfologi : Jurnal Ilmu Pendidikan, Bahasa, Sastra dan Budaya, 2024)
The problem in this research is whether the application of role playing techniques through group guidance is effective in increasing the self-esteem of class IX A students at SMPK St. Yoseph Noelbaki for the 2023/2024 academic year? The aim of this research is to determine the effectiveness of applying role playing techniques through group guidance to increase the self-esteem of class IX A students at SMPK St. Yoseph Noelbaki Kupang 2023/2024 academic year The method used in this research is quantitative descriptive using pre-experimental design (one-group pretest-posttest design). The instruments used in this research were a self-esteem questionnaire and guidelines for implementing role playing techniques. The data analysis technique uses the t test formula. The results of data analysis show that the t_count value is 33.4268, while the t_table value at the 5% significance level is 2.132. Thus, the t_count>t_table value, this shows that the role playing technique through group guidance is effective in increasing the self-esteem of class IX A students at SMPK St. Yoseph Noelbaki Kupang 2023/2024 academic year. Based on the results of this research, the researcher provides suggestions to: 1) The Principal is expected to further increase collaboration with Guidance and Counseling teachers in the implementation of role playing techniques through group guidance in order to help increase students' self-esteem. 2) Guidance and Counseling Teachers are expected to continuously carry out activities applying role playing techniques through group guidance to increase students' self-esteem. 3) Students are expected to actively participate in participating in activities applying role playing techniques through group guidance to increased self-esteem.